The Increasing Age of TBI Patients at a Single Level 1 Trauma Center and the Discordance Between GCS and CT Rotterdam Scores in the Elderly - Garza, Nicholas; Toussi, Atrin; Wilson, Machelle; Shahlaie, Kiarash; Martin, Ryan (Frontiers in Neurology, 2020)
Introduction Traumatic brain injury (TBI) is frequently encountered in geriatric patients, but there is a paucity of data describing TBI in the elderly. Here, we show the age of patients with TBI is increasing at our medical center and discuss the relationship between age and injury severity with patient outcomes. Methods This is a retrospective analysis of 3,179 adult patients with TBI treated at the University of California, Davis Level 1 Trauma Center between 2009 and 2016. Age, Glasgow Coma Scale (GCS), and CT Rotterdam Scores were recorded. Age was analyzed as both a continuous and categorical variable (18-34, 35-50, 51-65, >65 years-old). Extended Glasgow Outcome Scale was obtained at 3 and 6 months and dichotomized into favorable and unfavorable outcomes. Multivariable general linear regression models, chi-square, logistic regression analyses and ANOVA were used for statistical analyses; a p-value less than .05 was considered significant. Results The mean age of patients was 52.2±21.9 years with a male predominance (69%). There was a significant trend (p=0.002) towards an increase in mean age each year, increasing by 4.4 years (p=0.008) over the course of the analysis. Older patients had a higher mean GCS compared to younger patients with the same CT Rotterdam score (p=0.027), this becoming more pronounced with worse CT Rotterdam scores. The >65 group had a 4-fold increased risk for unfavorable outcome when compared to the 18-34 group, this effect being most pronounced after mild TBI. Conclusions The mean age of TBI patients is increasing at our trauma center. The largest disparity in outcomes across age was seen in patients with a mild GCS and low CT Rotterdam scores, suggesting that these markers of injury severity may underestimate the severity of injury in the elderly population. This information highlights the need for clinical trials and validation of outcome markers in geriatric TBI.